On non-extinction in a Fleming-Viot-type particle model with Bessel drift - Kolb, Martin; Liesenfeld, Matthias (Electronic Journal of Probability)
Motivated by the work [6] of Mariusz Bieniek, Krzysztof Burdzy and Soumik Pal we study a Fleming-Viot-type particle system consisting of independently moving particles each driven by generalized Bessel processes on the positive real line. Upon hitting the boundary {0} this particle is killed and an uniformly chosen different one branches into two particles. Using the symmetry of the model and the self similarity property of Bessel processes, we obtain a criterion to decide whether the particles converge to the origin at a finite time. This addresses open problem 1.4 in [6]. Specifically, inspired by [6, Open Problem 1.5], we investigate the case of three moving particles and refine the general result of [6, Theorem 1.1(ii)] extending the regime of drift parameters, where convergence does not occur – even to values, where it does occur when considering the case of only two particles.

Persistence of autoregressive sequences with logarithmic tails - Denisov, Denis; Hinrichs, Günter; Kolb, Martin; Wachtel, Vitali (Electronic Journal of Probability)
We consider autoregressive sequences Xn = aXn−1 + ξn and Mn = max{aMn−1 , ξn} with a constant a ∈ (0, 1) and with positive, in- dependent and identically distributed innovations {ξk }. It is known that if P(ξ1 > x) ∼ d log x with some d ∈ (0, − log a) then the chains Xn and Mn are null recurrent. We investigate the tail behaviour of recurrence times in this case of logarithmically decaying tails. More precisely, we show that the tails of recurrence times are regularly varying of index −1 − d/ log a. We also prove limit theorems for Xn and Mn conditioned to stay over a fixed level x0. Furthermore, we study tail asymptotics for recurrence times of Xn and Mn in the case when these chains are positive recurrent and the tail of log ξ1 is subexponential.

Green Deals Gain Steam - Kengelbach, Jens; Keienburg, Georg; Söllner, Tobias; Wang, Yiran; Sievers, Sönke; Friedmann, Daniel; Nielsen, Jesper (BCG M&A Report 2022)

Do Green Deals Create Value? - Kengelbach, Jens; Friedman, Daniel; Keienburg, Georg; Degen, Dominik; Söllner, Tobias; Wang, Yiran; Sievers, Sönke (BCG M&A Report 2022)

Systematizing the lexicon of platforms in information systems: a data-driven study - Bartelheimer, Christian; zur Heiden, Philipp; Lüttenberg, Hedda; Beverungen, Daniel (Electronic Markets)
Abstract While the Information Systems (IS) discipline has researched digital platforms extensively, the body of knowledge appertaining to platforms still appears fragmented and lacking conceptual consistency. Based on automated text mining and unsupervised machine learning, we collect, analyze, and interpret the IS discipline’s comprehensive research on platforms—comprising 11,049 papers spanning 44 years of research activity. From a cluster analysis concerning platform concepts’ semantically most similar words, we identify six research streams on platforms, each with their own platform terms. Based on interpreting the identified concepts vis-à-vis the extant research and considering a temporal perspective on the concepts’ application, we present a lexicon of platform concepts, to guide further research on platforms in the IS discipline. Researchers and managers can build on our results to position their work appropriately, applying a specific theoretical perspective on platforms in isolation or combining multiple perspectives to study platform phenomena at a more abstract level.
Keywords: Management of Technology and Innovation; Marketing; Computer Science Applications; Economics and Econometrics; Business and International Management

Schärfung der Sinne. Josef Winklers Mikroästhetik im Kontext kleiner Prosaformen der Moderne - Öhlschläger, Claudia (Inter- und transmediale Ästhetik bei Josef Winkler)

Evaluating database systems relying on secure multiparty computation - Anonymous, A

Cost of Privacy-preserving SMPC Protocols for NN-Based Inference - Anonymous, A

Alfred Anderschs "Die Rote" mit Antonioni gelesen - Öhlschläger, Claudia (Das Italien des Alfred Andersch. Interkulturelle und intermediale Konstellationen)

Lattice Revocation Mechanisms - Lohse, Jan

Selective area heteroepitaxy of InAs nanostructures on nanopillar-patterned GaAs(111)A - Riedl, Thomas; Kunnathully, Vinay S.; Verma, Akshay Kumar; Langer, Timo; Reuter, Dirk; Büker, Björn; Hütten, Andreas; Lindner, Jörg (Journal of Applied Physics)
A process sequence enabling the large-area fabrication of nanopillar-patterned semiconductor templates for selective-area heteroepitaxy is developed. Herein, the nanopillar tops surrounded by a SiN x mask film serve as nanoscale growth areas. The molecular beam epitaxial growth of InAs on such patterned GaAs[Formula: see text]A templates is investigated by means of electron microscopy. It is found that defect-free nanoscale InAs islands grow selectively on the nanopillar tops at a substrate temperature of 425 °C. High-angle annular dark-field scanning transmission electron microscopy imaging reveals that for a growth temperature of 400 °C, the InAs islands show a tendency to form wurtzite phase arms extending along the lateral [Formula: see text] directions from the central zinc blende region of the islands. This is ascribed to a temporary self-catalyzed vapor–liquid–solid growth on [Formula: see text] B facets, which leads to a kinetically induced preference for the nucleation of the wurtzite phase driven by the local, instantaneous V/III ratio, and to a concomitant reduction of surface energy of the nanoscale diameter arms.
Keywords: General Physics and Astronomy

Size‐Dependent Strain Relaxation in InAs Quantum Dots on Top of GaAs(111)A Nanopillars - Riedl, Thomas; Kunnathully, Vinay; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

Democracy ≠ Democracy. Creating digital infographics to compare different democratic systems. - Janzen, Thomas (Englisch betrifft uns)

Geschlechtsidentität - Krämer, Anike (Fachlexikon der Sozialen Arbeit)

Sexuelle Orientierung - Krämer, Anike (Fachlexikon der Sozialen Arbeit)

Qualifizierung von Studierenden des Grund- und Förderschullehramts für Inklusion in Schule und Unterricht - Franzen, Katja; Albers, Timm; Hellmich, Frank (Qualifizierung für Inklusion. Grundschule)
Inklusion ist als Thema aus dem deutschen Bildungssystem nicht mehr wegzudenken und trotzdem stellt sie weiterhin eine Herausforderung auf unterschiedlichen Ebenen dar. Die Qualifizierung der pädagogischen Fachkräfte ist dabei neben der Bereitstellung adäquater Rahmenbedingungen als ein besonders wichtiges Handlungsfeld zu betrachten. Die Bände der Reihe „Qualifizierung für Inklusion“ greifen den bestehenden Forschungs- und Entwicklungsbedarf auf und geben einen Überblick über die Ergebnisse der vom BMBF im Rahmen des Programms „Qualifzierung der pädagogischen Fachkräfte für inklusive Bildung“ geförderten Forschungsprojekte. Adressiert werden damit sowohl Wissenschaftler:innen als auch mit dem Themenfeld Inklusion befasste Personen und Institutionen der Aus-, Fort- und Weiterbildung, der Bildungsadministration und der Bildungspolitik. Der zweite Band der Reihe versammelt die Vorstellung von Projekten, Ergebnissen und Materialien, die sich dem Bildungsbereich der Grundschule zuordnen lassen. Die Reihe besteht aus drei weiteren Bänden, in denen die Ergebnisse zur Qualifizierung für Inklusion im Elementarbereich (Band 1), in der Sekundarstufe (Band 3) sowie in der Berufsschule, Hochschule und Erwachsenenbildung (Band 4) vorgestellt werden.

Primary School Principals’ Views on the Required Conditions for a Successful Implementation of Inclusive Education - Görel, Gamze; Hellmich, Frank (Australasian Journal of Special and Inclusive Education)
Abstract Following the United Nations Convention on the Rights of Persons With Disabilities, questions concerning the joint education of students with and without special educational needs remain to be answered. Currently, there is a need for knowledge about the necessary conditions for a successful implementation of inclusive education. Thus, the aim of the present study is to identify conditions for the implementation of inclusion that are seen as necessary by primary school principals. Therefore, 32 primary school principals were interviewed. The results of the interview study reveal that factors like personnel, financial and material resources as well as building infrastructure in primary schools are seen as important requirements for the successful realisation of inclusive education. Apart from that, the importance of attitudes towards inclusion and sociopolitical conditions for the realisation of inclusion became apparent. Further conditions, which are mentioned from the interviewed principals’ point of view, are related to teacher training, appropriate class sizes and, for example, opportunities for exchanging information. The results of the study indicate that there are essential obstacles as perceived by primary school principals that can impede the implementation of inclusion in primary schools.
Keywords: General Engineering

Qualität der Erfahrungen aus dem inklusiven Unterricht und Selbstwirksamkeitsüberzeugungen von Grundschullehrkräften - Franzen, Katja; Moschner, Barbara; Hellmich, Frank (Sonderpädagogik – zwischen Dekategorisierung und Rekategorisierung)

Adaptiver Unterricht in der (inklusiven) Grundschule aus der Perspektive von Lehrkräften - Löper, Marwin Felix; Hellmich, Frank (Sonderpädagogik – zwischen Dekategorisierung und Rekategorisierung)

FRIEND-SHIP Intervention Program – The Handbook - Aroni, Katerina; Toulia, Anastasia; Alves, Sílvia Regina Gonçalves; Hassani, Sepideh; Heidrich, Franziska Anna; Franzen, Katja; Görel, Gamze; Löper, Marwin Felix; Aguiar, Teresa; Silveira-Maia, Mónica; Sanches-Ferreira, Maria Manuela Pires Sanches; Hellmich, Frank; et al.